The effectiveness of biofilter for reducing TSS and ammonia content in oil palm industry’s liquid waste - Sitepu, Kelvin Suhermanta; Harahap, Sampe; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The oil palm liquid waste is rich in TSS and ammonia and thus need to be processed before being flown to environment. A study aims to reduce the TSS and ammonia in that waste has been conducted in April - May 2018. The palm oil liquid waste (135 L) was kept in an anaerob system (with gravel, sand and palm fiber media) for 10 days. The waste was then flown to an aerobic system (with charcoal and palm fiber media) for 10 days and finally the waste was treated in a phytoremediation pond that was completed by Salvinia molesta for 15 days. By the end of the experiment, the TSS reduced from 2,020 mg/L to 237mg/L (the effectivity was 88.26%), while the ammonia reduced from 31.14 mg/L to 4.6 mg/L (the effectivity was 85.22% ). Other water quality parameters such as pH was normal (6-7) and DO was improved, from 0.42 mg/L to 2.18 mg/L. The treated waste was then used for rearing Oreochromis niloticusfingerlings for 96 hours and survival rate of the fish was 100%. Based on data obtained, it can be concluded that the combination of anaerob-aerob systems and phytoremediation using Salvinia molesta is effective to reduce the TSS and ammonia content in the oil palm industry liquid waste. Keyword: waste water, contaminated waste, batch system, waste management